Cultivation of king eryngii (Pleurotus eryngii (DC. ex Fr.) Quel.) isolates on various local agro-residues - Akyuz, Mehmet; Kirbag, Sevda (Springer Heidelberg, 2024)
The increase in the world population and the rapid consumption of natural products have created problems in meeting nutritional needs. In addition, there are serious environmental problems in the use, evaluation, and disposal of bio-waste products arising from agricultural activities. The evaluation of agricultural wastes in mushroom cultivation, which is an important branch of the agricultural economy in recent years, is important in solving these problems. Cultivated mushrooms grown on some agricultural wastes have the potential to be an important food source. This study aims to investigate the possibility of using bean pods (Phaseolus vulgaris L. (BP)), chickpea pods (Cicer arietinum L. (CP)), lentil straw (Lens culinaris Medik. (LS)), and barley straw (Hordeum vulgare L. (BS)) residues in the culture of three strains of Pleurotus eryngii obtained from the Dfizce University (PED), Selcuk University (PES), and Hacettepe University (PEH), Turkey. Four types of compost were prepared, consisting of a mixture of BP +CP (1:1), BP +LS (1:1), BP +BS (1:1), and BP. The shortest mycelium growing day was 14.7 days on BP +CP (1:1) in PES and the longest one was 17.7 days on BP +LS (1:1) in PEH. The shortest primordia initiation days were 24.0 and 24.3 days on BP and BP +CP (1:1) in PEH and the longest ones were 32.3, 33.7, and 34.7 days on BP+ LS (1:1), BP+ BS (1:1), and BP in PED. P. eryngii cultivation continued for about 72-87 days, during which an average of three products were harvested. In total yield, the minimum yield (24.3-26.7 g) per 100 g of material (70% moisture) was observed in PED and the maximum yield (28.7-33.3 g) in PEH and PES. As a result, the isolates (PES and PEH) used in the study were found to be effective on earliness primordia formation and yield. Therefore, cheaper and locally available alternative substrates, including BP, CP, LS, and BS wastes, can be tried for the production of P. eryngii and other culture mushrooms.
Keywords: Lignocellulosic residues; Mushroom growing; Pleurotus eryngii; King oyster; Mushroom biotechnology